Late Quaternary fingerprints of precession and sea level variation over the past 35 kyr as revealed by sea surface temperature and upwelling records from the Indian Ocean near southernmost Sumatra. (15th December 2016) - Li, Ziye; Shi, Xuefa; Chen, Min-Te; Wang, Houjie; Liu, Shengfa; Xu, Jian; Long, Haiyan; Troa, Rainer Arief; Zuraida, Rina; Triarso, Eko
Abstract: We report high-resolution paleoclimatic reconstructions using isotope, alkenone sea surface temperature (SST), productivity, and terrigenous proxy variations over the past 35 kyr from core SO184-10043 (07°18.57′S, 105°03.53′E) in the eastern tropical Indian Ocean offshore of southernmost (S) Sumatra. The core was retrieved at 2171 m water depth, from the monsoon driven seasonal upwelling area off southernmost Sumatra. Our paleoclimatic reconstructions show that an enhanced marine productivity was closely linked to strengthening of coastal upwelling during the increases of boreal summer insolation and associated southeastern (SE) monsoon strength, with pronounced semi-precession cycles (∼11 kyr). In contrast, our record of alkenone SSTs shows glacial to interglacial, a sea-level variation, but this fluctuates at dominant precession cycles (∼21 kyr). We also observed four SST "plateaus" with relatively warmer hydrographic stability in our records over the past 35 kyr: 32-27 ka, 24-20 ka, 17-12 ka, and 9-4 ka. The time scale of each plateau is ∼4-6 kyr. Our study indicates that since the last glacial maximum (LGM), the sea level rise has been responsible for the Sunda shelf flooding and the Indonesian Throughflow (ITF) from the South China Sea (SCS) to the eastern Indian Ocean, leaving a dominant fingerprint of a glacial to interglacial increase in SSTs since ∼9.5 ka We further argue that the a most recent centennial to millennial scale cooling at ∼3.5 ka observed in our SST record is a widespread event in the tropical Pacific, which has implications for advancing our understanding of the climate dynamics of the tropical oceans at these time scales.